PERSEPSI PASIEN TERHADAP MUTU PELAYANAN DI UNIT FARMASI RUMAH SAKIT PROF. DR. TABRANI PEKANBARU - Salim, Agus; Hafizah; Yuliana, Anastasya Shinta (LPPM Universitas Awal Bros, 2023)
In an effort to improve pharmaceutical services, it is also necessary to improve the quality of services provided. This is due to the increasingly complex needs of the community for health. Basically, the quality of health services refers to the level of health services in creating a sense of satisfaction for each patient. The more perfect the satisfaction, the better the quality of health services. The purpose of this study was to determine the relationship between patient perceptions of service quality in the outpatient pharmacy unit of Prof. Hospital. Dr. Tabrani Pekanbaru. This type of research is quantitative with a cross sectional design. This research was conducted on 15 September-23 September 2022 at the Pharmacy Unit of Prof. Hospital. Dr. Tabrani Pekanbaru. Respondents in this study amounted to 72 people with purposive sampling method. The results showed that the patient's perception of the Tangible dimension was 0.480. For the patient's perception of the Reabilty dimension of 0.239, Responsiviness of 0.197, Assurance/Guarantee of 0.237, patient's perception of Empathy of 0.513. So the five hypotheses are significant because the value > 0.05 obtained from data processing through the SPSS 26.0 application. The conclusion of this study shows that the Tangible, Reability, Responsiviness, Assurance, Empathy variables have a significant relationship to the patient's perception. Suggestions from this study should further researchers be able to conduct research, it would be better to use quantitative methods and use the Mix Method.